2016
DOI: 10.21512/comtech.v7i1.2220
|View full text |Cite
|
Sign up to set email alerts
|

Impelementation of Information Technology Service Management at Data And Information System Center of XYZ University

Abstract: Information Technology (IT) is increasingly progressing. Nowadays, the success of a business of the organization/company is highly dependent on the IT infrastructure used. Therefore, organizations/companies have to manage their IT service to be optimal to their customers. Looking at this matter and the increasing dynamics of XYZ University, then Data and Information System Center (Pusdatin) - an IT provider of XYZ University began implementing IT Service Management (ITSM) from 2013 using the latest version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Research that has been conducted in educational institutions has received more attention since 2015 to date, especially educational institutions located in East Java Province with a total of 14 studies. Research with the educational domain is found in both universities [172], [185], [186], or high schools [108], and this is natural because most of these researchers are academics on campus, so there is the possibility of selecting objects in the Education unit due to easier access to data.…”
Section: Rq3: What Is the Most Widely Used Itsm Framework In Indonesia?mentioning
confidence: 99%
“…Research that has been conducted in educational institutions has received more attention since 2015 to date, especially educational institutions located in East Java Province with a total of 14 studies. Research with the educational domain is found in both universities [172], [185], [186], or high schools [108], and this is natural because most of these researchers are academics on campus, so there is the possibility of selecting objects in the Education unit due to easier access to data.…”
Section: Rq3: What Is the Most Widely Used Itsm Framework In Indonesia?mentioning
confidence: 99%
“…These experts investigate the current practices and recommend a collection of changes along with guidelines by benchmarking a state-of-the-art standard for the improvement of their existing practices and procedures. Other than that, the government of the United Kingdom has officially developed a framework that comprises of practices that organizations can follow themselves to improve the software processes [12].…”
Section: Introductionmentioning
confidence: 99%